D8 Open Data for Agriculture Presentation by Indira Yerramareddy, IFPRI, Dataverse - Yerramareddy, Indira (2013)
Presentation by Indira Yerramareddy, IFPRI at the D8 Open Data for Agriculture Side event at IFPRI on May 1, 2013.